The Influence of Rewards and Motivation on Leaders' Interest in Participating in Accreditation Programs - Waluyo, Jarot; Herlambang, Toni; PutuMartini, Ni Nyoman; Qomariah, Nurul (Budapest International Research and Critics University, 2024)
Accreditation is an effort to assess whether an institution is worthy of providing services to users. Accreditation assessment is feasible so that the institution is worthy and guaranteed in providing services in any field. The purpose of this study was to determine the impact of rewards and motivation in influencing interest in participating in the accreditation program on PAUD leaders in Jember. All PAUD leaders in Jember became the population with a total of 1804 people. The number of samples was 327 leaders using the Slovin formula. The analysis tools were descriptive statistics, validity and reliability tests and direct influence tests. Rewards have a direct effect on interest in participating in accreditation. Motivation has an impact on interest in participating in accreditation.